Remembering the South African War Britain and the Memory of the Anglo-Boer War, from 1899 to the Present - Donaldson, Peter (Liverpool University Press, 2013)
The experience of the South African War sharpened the desire to commemorate for a number of reasons. An increasingly literate public, a burgeoning populist press, an army reinforced by waves of volunteers and, to contemporaries at least, a shockingly high death toll embedded the war firmly in the national consciousness. In addition, with the fallen buried far from home those left behind required other forms of commemoration. For these reasons, the South African War was an important moment of transition in commemorative practice and foreshadowed the rituals of remembrance that engulfed Britain in the aftermath of the Great War. This work provides the first comprehensive survey of the memorialisation process in Britain in the aftermath of the South African War. By uncovering the themes and myths that underpinned these interpretations of the war, shifting patterns in how the war was represented and conceived are revealed.